Estimation of above Ground Biomass and Soil Organic Carbon Pools in Dry Forests of Palakonda Hill Ranges, Southern Eastern Ghats - Sreedhar Rao, P.; Venkata Ramana, C.; Sridhar Reddy, M. (Indian Forester, 2023)
The present study deals with the estimation of above, below ground and soil carbon stocks in dry forests of Palakonda hill ranges. Tree inventory was carried out by enumerating all trees ≥30 cm gbh in two forest sites – dry deciduous (DD) and dry thorn (DT) forest site. Above ground biomass (AGB) was estimated by using volume equations provided by Forest Survey of India; below ground biomass (BGB) was estimated by Cairns equation; and soil organic carbon values were determined for samples collected at 0-10 cm and 10-20 cm depths. Tree inventory has resulted a range of 21-43 tree 2 species, 227-337 tree density (individuals/ha), basal area 2.83 m2/ha- 6.26 m2/ha in DT and DD site respectively. Majority of tree individuals occurred in lower gbh class corresponding to79.6% in DD site and 91.25% in DT site. The estimated AGB was 134.3 t/ha in DD and 73.37 t/ha in DT site. Pterocarpus santalinus was the top rank species contributing 28.6% of total AGB in DD site and 25.4% in DT site and the top ten species have accounted for >90% of the total AGB in both the study sites. The mean SOC value was 1.51% in DD site and 0.55% in DT site resulting in Soil carbon stock of 42.08±12.05t/ha in DD forest site and (28.37±8.35) t/ha in DT site. The highest carbon stock was recorded in the AGB followed by carbon stock stored as soil organic carbon in soils up to 30 cm depth and carbon stock in BGB. The AGB in the forest is influenced by tree species composition and their girth class distribution. Soil organic carbon storage potential was found to be influenced by bulk density and soil texture.